Odpowiedź :
Odpowiedź:
64x² - 49 = 0
Korzystamy ze wzoru skróconego mnożenia (a² - b²) = (a - b)(a +b)
64x² - 49 = (8x - 7)(8x + 7)
(8x - 7)(8x + 7) = 0
8x -7 = 0 ∨ 8x + 7 = 0
8x = 7 ∨ 8x = - 7
x = 7/8 ∨ x = - 7/8
∨ - znaczy "lub"
x² - 10x + 25 = 0
Korzystamy ze wzoru skróconego mnożenia (a - b)² = a² - 2ab + b²
x² - 10x + 25 = (x - 5)²
(x - 5)² = 0
x - 5 = 0
x = 5
Odpowiedź:
[tex]64x^{2} - 49 = 0[/tex]
[tex](8x - 7)(8x+7) = 0[/tex]
8x - 7 = 0 ∨ 8x + 7 = 0
8x = 7 ∨ 8x = -7
[tex]x = \frac{7}{8} \ \ \ \vee \ \ \ x = -\frac{7}{8}[/tex]
[tex]x^{2} - 10x + 25 = 0[/tex]
[tex](x - 5)^{2} = 0[/tex]
x - 5 = 0
x = 5